2001
DOI: 10.1176/appi.ajp.158.3.494
|View full text |Cite
|
Sign up to set email alerts
|

Right Frontal Hypergyria Differentiation in Affected and Unaffected Siblings From Families Multiply Affected With Schizophrenia: A Morphometric MRI Study

Abstract: In this family cohort study, the postmortem finding of right-sided hypergyria in subjects with schizophrenia was replicated in vivo with magnetic resonance imaging. This observation provides further support for a neurodevelopmental mechanism in the pathogenesis of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 9 publications
3
49
1
2
Order By: Relevance
“…Moreover, in addition to findings of abnormal gyrification complexity in schizophrenia (14)(15)(16), there have also been reports of abnormal temporal lobe sulcalgyral patterns in schizophrenia (12). Using cortical complexity measures, Narr and colleagues (17) found a disturbance in the patterns of gyral asymmetries in the frontal regions in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in addition to findings of abnormal gyrification complexity in schizophrenia (14)(15)(16), there have also been reports of abnormal temporal lobe sulcalgyral patterns in schizophrenia (12). Using cortical complexity measures, Narr and colleagues (17) found a disturbance in the patterns of gyral asymmetries in the frontal regions in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…The gyrification index is considered a quantitative assessment of gyrification (13) and provides a measure of overall cortical folding. A postmortem study of the gyrification index in schizophrenia showed right-sided hypergyria in the pre-frontal region in male patients (14), a finding that was subsequently replicated in vivo with MRI (15). In contrast, an MRI study of male schizophrenic patients showed lower than normal gyrification in the whole left hemisphere (16).…”
mentioning
confidence: 95%
“…19 Such increases could also be considered reflective of increased prefrontal cortical folding, as measured by the gyrification index, which can be seen as an indirect measure of axonal connectivity. 66 Increased prefrontal gyrification has been demonstrated in patients with schizophrenia 67 and has been shown to be predictive of transition to psychosis in high-risk cohorts. 68 …”
Section: Discussionmentioning
confidence: 99%
“…Prefrontal hypergyria (higher GI) (Vogeley et al 2000(Vogeley et al , 2001Falkai et al 2007 ;Harris et al 2007), lower prefrontal and global (Sallet et al 2003 ;Cachia et al 2008) GI, as well as negative findings (Highley et al 2003) have been reported. Gyrification abnormalities have been reported to be present before adult illness onset (Harris et al 2004a, b).…”
Section: Introductionmentioning
confidence: 93%